Effect of Baseline Symptom Manifestations on Retention in Care and Treatment among HIV-Infected Patients in Nigeria. (4th February 2020) - Adeola, Juliet; Badejo, Okikiolu Abimbola; Ahonkhai, Aimalohi; Okonkwo, Prosper; Aboh Akande, Patrick; Evans, Charlesnika Tyon; McHugh, Megan; Pierce, Leslie; Ahmed, Isah; Jolayemi, Toyin; Ladi Akinyemi, Babatunde; Onwuatuelo, Ifeyinwa; et al.
Background: Symptom management is an important component of HIV care. But symptom patterns and how they affect engagement with HIV care and treatment services have not been adequately explored in the era of increased HIV treatment scale-up. We investigated the relationship between symptom patterns among people living with HIV (PLHIV) and 12 months retention in care, within the context of other clinical and demographic characteristics. Methods: Retrospective cohort analysis of 5114 PLHIV receiving care within a large HIV treatment program in Nigeria. We assessed the prevalence and burden of baseline symptoms reported during routine clinic visits from January 2015 to December 2017. Multivariable regression was used to identify relationships between 12-month retention and symptom dimensions (prevalence and burden) while controlling for demographic and other clinical variables. Results: Increasing symptom burden was associated with higher likelihood of retention at 12 months (adjusted odds ratio [aOR] = 1.19 [95% confidence interval, CI: 1.09-1.29]; P < .001) as was the reporting of skin rashes/itching symptom (aOR = 2.59 [95% CI: 1.65-4.09]; P < .001). Likelihood of retention reduced with increasing World Health Organization (WHO) Clinical staging, with CD4 ≥500 cells/mL and self-reported heterosexual mode of HIV transmission.Conclusions : Symptom dimensions and standardized clinical/immunological measures both predicted retention in care, but effects differed in magnitude and direction. Standardized clinical/immunological measures in HIV care (eg, WHO clinical staging and CD4 count categories) can mask important differences in how PLHIVs experience symptoms and, therefore, their engagement with HIV care and treatment. Symptom management strategies are required alongside antiretroviral treatment to improve outcomes among PLHIV, including retention in care.